The Validity and Reliability of Self-Assessment on Reading Comprehension at Junior High School - Irfan Susiyana Putra (Eduvest - Journal of Universal Studies, 2024)
This study aims to investigate whether self-assessment is valid and reliable for assessing reading comprehension. Participants in this study were 18 male students and 20 female students from a junior high school. This research is quantitative research designed with mixed methods, causal-comparative and correlative research. Independent t test was used to analyse validity, and correlation analysis was used to test reliability. Researchers used two instruments in the data collection process, (1) a self-assessment questionnaire and (2) a reading comprehension test. This research concludes that 1) self-assessment is valid because male and female students do not carry out self-assessment differently. This means that gender is not a construct irrelevance factor that affects the validity of self-assessment. 2) Self-assessment is reliable or consistent because there is a positive correlation between self-assessment scores and reading comprehension tests. Two statistical analyses were used to examine the data collected. First, independent t-tests were used to investigate the influence of gender on self-assessment scores. From data analysis, this study revealed that there were no significant differences between male and female students in self-assessment. This means that gender is not proven to be an irrelevant factor to the construct that affects validity. Thus, the self-assessment of reading comprehension in junior high school is valid.